1969
DOI: 10.1002/anie.196909821
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Solvent Catalysis; N,N,N′,N′‐Tetramethyl‐2,3‐dimethoxy‐1,4‐butanediamine, a New Chiral Medium

Abstract: Conversion into the diamide (3b) .0 OC; [ a ]~ = 42.7 (c = 3.0 in CzH50H)], esterification to give (3c) [(CH&S04, m.p.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1974
1974
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…This observation supported the view that reduction occurred only in cages containing the chiral inductor. Had there been intermolecular reduction (to yield racemic products) in cages that do not contain the chiral inductor the ee would have increased with increased loading levels of the chiral inductor While the ee obtained in this study is the highest amongst the thus far reported examples of photoreduction of achiral ketones, 19 unfortunately we are unable to develop a model that could be used to predict the extent of chiral induction within a zeolite. Several observations suggest that one must include the alkali ion in any mechanistic understanding of the asymmetric induction process within zeolites.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This observation supported the view that reduction occurred only in cages containing the chiral inductor. Had there been intermolecular reduction (to yield racemic products) in cages that do not contain the chiral inductor the ee would have increased with increased loading levels of the chiral inductor While the ee obtained in this study is the highest amongst the thus far reported examples of photoreduction of achiral ketones, 19 unfortunately we are unable to develop a model that could be used to predict the extent of chiral induction within a zeolite. Several observations suggest that one must include the alkali ion in any mechanistic understanding of the asymmetric induction process within zeolites.…”
Section: Discussionmentioning
confidence: 67%
“…One of the earliest reports of the use of amines as chiral reagents is by Seebach and coworkers in the solution phase photopinacolization of aromatic ketones. 19 A mixture of 1 : 5 chiral amine to pentane as solvent at −72 • C gave about 23.5% ee in the DL-pinacol formed from acetophenone. It is important to note that in our studies no pinacol was obtained and in the majority of the cases the only product is the corresponding alcohol and the ee obtained within zeolites is in the range between 22-68%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low enantioselectivity (6% ee) is obtained, even when an excess of L7 (3 equiv) is employed in the reaction. 20…”
Section: Scheme 4 Enantioselective Addition Of Grignard Reagents To mentioning
confidence: 99%
“…Organolithium compounds are frequently used in organic syntheses as strong bases for lithiations and as powerful nucleophiles for C–C bond formations . Despite the fact that n -butyllithium ( n- BuLi) and other organolithium compounds are extensively employed reagents, comparatively few chirally modified organolithium complexes have been structurally characterized. , Structural analyses of enantiopure n- BuLi aggregates in solution and in the solid state ,, can provide explanations for reactivities and selectivities . Structural elucidations of these aggregates can also be crucial for a more rational design of new and more efficient chiral organolithium compounds for asymmetric syntheses .…”
Section: Introductionmentioning
confidence: 99%